Tracing detrital signature from Indochina in Peninsular Malaysia fluvial sediment: Possible detrital zircon recycling into West Borneo Cenozoic sediments. (15th September 2021) - Quek, Long Xiang; Lee, Tung-Yi; Ghani, Azman A.; Lai, Yu-Ming; Roselee, Muhammad Hatta; Lee, Hao-Yang; Iizuka, Yoshiyuki; Lin, Yu-Ling; Yeh, Meng-Wan; Amran, Muhammad Amiruddin; Rahmat, Rezal
Graphical abstract: Highlights: Malayan Southeast Coastal Zone recycled detrital zircon derived from Indochina. Mid-Cenozoic Sundaland paleoriver carried detritus from Malaya to West Borneo. West Borneo Cenozoic sediments' Indochina detrital zircon signature was from Malaya. Abstract: Although Peninsular Malaysia abundant Permo-Triassic Malayan granitic plutons and volcanics (292–198 Ma) generate an enormous volume of detrital zircons that masks other detrital sources in fluvial sediments, there are suggestions that Peninsular Malaysia could recycle detrital zircons from Indochina (through Jurassic-Cretaceous strata) to other parts of Sundaland by paleoriver after the Indochina-Sundaland sediment link diminishes in the Cenozoic. As there is insufficient data to prove this, we compiled our new detrital zircon U-Pb isotopic data from modern river sands in Peninsular Malaysia with all available data to create a dataset that revealed five detrital zircon age pattern zones: (1) Northeast Coastal Zone (~73 Ma and ~223 Ma), (2) Mid-East Coastal Zone (~236 Ma and ~280 Ma), (3) Southeast Coastal Zone (~170 Ma, ~243 Ma, ~291 Ma, 400–416 Ma and 1545–1852 Ma), (4) Central Zone (~220 Ma) and (5) Mid-West Coastal Zone (~227 Ma and 1105–1173 Ma). All detrital age pattern zones show a clear detrital contribution from Malayan granitoids and volcanics. However, the Southeast Coastal Zone also shows significant contributions from Jurassic-Cretaceous strata in the northwest, e.g. Bertangga and Gerek sandstones, making them comparable with sources from Indochina and Lower Cretaceous strata in Singapore. We suggest a defunct drainage during Paleogene which transports the eroded sediments from the Jurassic-Cretaceous strata in the northwest to the sink in the southeast coast of Peninsular Malaysia recycled "Indochina signature" detrital zircons. If the sink connects with the Sundaland paleoriver system, it might contribute to the "Indochina signature" detrital provenance in West Borneo.